Microbial response to single‐cell protein production and brewery wastewater treatment. Issue 1 (16th May 2014) - Lee, Jackson Z.; Logan, Andrew; Terry, Seth; Spear, John R.
Summary As global fisheries decline, microbial single‐cell protein (SCP) produced from brewery process water has been highlighted as a potential source of protein for sustainable animal feed. However, biotechnological investigation of SCP is difficult because of the natural variation and complexity of microbial ecology in wastewater bioreactors. In this study, we investigate microbial response across a full‐scale brewery wastewater treatment plant and a parallel pilot bioreactor modified to produce an SCP product. A pyrosequencing survey of the brewery treatment plant showed that each unit process selected for a unique microbial community. Notably, flow equalization basins were dominated by Prevotella, methanogenesis effluent had the highest levels of diversity, and clarifier wet‐well samples were sources of sequences for the candidate bacterial phyla of TM7 and BD1‐5. Next, the microbial response of a pilot bioreactor producing SCP was tracked over 1 year, showing that two different production trials produced two different communities originating from the same starting influent. However, SCP production resulted generally in enrichment of several clades of rhizospheric diazotrophs of Alphaproteobacteria and Betaproteobacteria in the bioreactor and even more so in the final product. These diazotrophs are potentially useful as the basis of a SCP product for commercial feed production.